(Post)apartheid Conditions - Hook, D. author. aut Link
X, 242 p.
Keywords: (Post)apartheid Conditions: Psychoanalysis and Social Formation advances a series of psychoanalytic perspectives on contemporary South Africa, exploring key psychosocial topics such as space-identity, social fantasy, the body, whiteness, memory and nostalgia.